Experimental methodologies and diagnostic procedures for acute hepatopancreatic necrosis disease (AHPND) - Devadas, S.; Banerjee, S.; M.Yusoff, F.; Bhassu, S.; Mohamed Din, Mohamed Shariff (Elsevier, 2019)
Acute hepatopancreatic necrosis disease (AHPND) is an emerging disease that has caused mass mortality in shrimp in many countries in Asia and South America. A new strain of Vibrio parahaemolyticus (VpAHPND), carrying one or more extrachromosomal ~70 kbp plasmids that encode homologues of the Photorhabdus insect-related (Pir) binary toxins (PirAvp and PirBvp) is the causative agent of AHPND. Bioassay challenges using immersion, reverse gavage and per os (feeding) treatments have been shown to induce the pathology characteristics of AHPND in experimentally infected shrimp. Moreover, a number of polymerase chain reaction (PCR) methods have been found to facilitate early detection of the disease. However, non-V. parahaemolyticus species close to Vibrio harveyi, Vibrio owensii and Vibrio campbellii have recently been identified as carrying pVA1-like plasmids, signifying that these plasmids are capable of being transmitted to different Vibrio species. AHPND is thus a threat and a serious concern for the aquaculture industry. Against this background, this paper presents an overview of experimental methodologies and diagnostic procedures for AHPND. It also includes fundamental findings related to the disease as guidelines which may be useful for further experimental work on AHPND and other similar shrimp diseases.